The Effect of the Discovery Learning Model on the Learning Outcomes of Fourth-Grade Students in Natural and Social Sciences - Ivo Monica Situmorang; Regina Sipayung; Rumiris Lumban Gaol; Darinda Sofia Tanjung; Jhonas Dongoran (International Journal of Research in Education, 2026)
This study examined the effect of the Discovery Learning model on the learning outcomes of fourth-grade students in Natural and Social Sciences at SD Negeri 060938 Medan Johor. A quantitative pre-experimental approach using a One-Group Pretest–Posttest Design was employed. The participants were 21 fourth-grade students selected through total sampling. Data were collected through achievement tests, a questionnaire, and documentation, and analyzed using descriptive statistics, the Shapiro–Wilk normality test, Pearson Product–Moment correlation, the coefficient of determination, and the t-test with IBM SPSS Statistics Version 25. The findings showed that the mean score increased from 52.76 on the pretest to 83.80 on the posttest. The data were normally distributed (Sig. = 0.413). Pearson correlation analysis revealed a very strong positive relationship between the Discovery Learning questionnaire score and learning outcomes (r = 0.969, p < 0.001). The coefficient of determination indicated that 93.9% of the variance in learning outcomes was explained by the implementation of Discovery Learning, while the t-test confirmed a significant positive effect (t = 17.047, p < 0.001). These findings indicate that Discovery Learning effectively improves students' learning outcomes in Natural and Social Sciences. This study contributes contextual evidence supporting the implementation of the Merdeka Curriculum by demonstrating the effectiveness of Discovery Learning in promoting student-centered learning at SD Negeri 060938 Medan Johor.